Ultrasound therapy in the management of temporomandibular joint disorders - Asan Mohamed Faizal; Hegde Shruthi; Subhas Babu G.; Ajila Vidya; Pandita Viabhav (Medicinski fakultet i Klinika za stomatologiju, Niš, 2023)
Introduction: Temporomandibular joint disorder (TMD) is a collective term given to the disorders affecting the Temporomandibular joint (TMJ), masticatory muscles and their related structures. The aetiology of TMD is complex and their management includes various invasive and non-invasive methods. The increasing trend in non-invasive, non-pharmacological interventions for the management of TMJ pain has led to the development of modalities of physical therapy. Ultrasound is an electrophysical treatment modality used in the management of TMD. The aim of this study is to provide an insight into ultrasound based treatment modalities used for the effective management of TMD. Materials and methods: Electronic database search was carried out in Google Scholar and PubMed using the search terms "ultrasound therapy", "therapeutic ultrasound" and "temporomandibular joint disorders". The results obtained from the database search were screened and included for the review. Commonly used therapeutic ultrasound methods in the management of temporomandibular joint disorders with the treatment protocols, advantages, limitations and other factors to be considered for an effective treatment outcome is discussed in the present review. Conclusion: Various new ultrasound-based TMJ therapeutic modalities may be developed in the near future.